Study usage expansion of quick response (QR) cross border In Yogyakarta - Susilo, Y Sri; Herawan, Jonathan Ersten; Dwi Putranto, Laurensius Farel (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
This study aims to provide policy recommendations that will be taken into consideration by stakeholders in Yogyakarta in an effort to accelerate the use of Quick Responses (QR) cross border by tourist from Malaysia in Yogyakarta, both in the short and long term. This study guided by a several plan which consist of 4 policy recommendations such as tax refunds for hotel service transactions, free entry for cultural heritage sites, tourism triangle future network, and QR cross border redesign. This study also hinted at the technical description, potential and limitations of each policy and concluded that the this plan is a potential alternative policy to take advantage of the economic momentum from Malaysian tourist visits in Yogyakarta to support Yogyakarta economic development in the long term.